Social Management of Municipal Development Councils, Rio Grande do Sul (Revista LIDER, 2020)
The study analyzes social management with citizen participation, dialogue, and deliberation in the Municipal Development Councils of the Northwest Regional Development Council (CoredeNORC) of the State of Rio Grande do Sul, Brazil. The methodology used was a qualitative approach in order to identify the effective practice of the concept of social management with deliberative citizenship through interviews with the actors involved in the process and the analysis of the legislation. The results showed a clear evolution of these spaces in the management of decentralized decision-making processes.